Farmakokinetika Flavonoid Ekstrak Daun Tin pada Plasma Darah Tikus (Universitas Negeri Semarang, 2022)
Fig leaves are used in medicine. Fig leaves containt flavonoids that are important for the body because have antioxidant activity to prevent oxidative stress and various ROS-related diseases. Fig leaf extract must qualify the requirements of clinical trials to strengthen data and information in the context of developing herbal medicine industry. The variable observed was the profile of flavonoid levels in rat blood plasma through pharmacokinetic parameters, namely Cmax, Tmax, T1/2, AUC, K and absorbtion speed. The research design used is an observational design with the time series method. Fasted rats were given 800 mg of fig leaf extract orally. Plasma flavonoid levels was analyzed using HPLC-UV-VIS with rutin as standard at time series 0, , 1, 2, 4, 6, 12, and 24 hours. The results of administration of fig leaf extract were absorbed and found in plasma Cmax 0.016 mg/ml with Tmax after 4 hours of oral administration, with a half-life (t1/2) 7.5 h and AUC 0.216 mg h/ml. Based on the plasma flavonoid levels data, the value of absorption speed 0.21 mg/h and the elimination speed (K) 0.092 mg/hour were obtained. Fig leaf extract was absorbed faster and eliminated from the body longer. Daun tin digunakan dalam pengobatan. Daun tin mengandung flavonoid yang penting bagi tubuh karena memiliki aktifitas antioksidan untuk mencegah stress oksidatif dan berbagai penyakit yang berhubungan dengan ROS. Ekstrak daun tin harus memenuhi syarat uji klinik untuk memperkuat data dan informasi dalam rangka pengembangan industri obat herbal. Variabel yang diamati adalah profil kadar flavonoid dalam plasma darah tikus melalui parameter farmakokinetik yaitu Cmax, Tmax, T1/2, AUC, K dan Ka. Rancangan penelitian yang digunakan adalah rancangan observasional dengan metode time series. Tikus yang sudah dipuasakan diberi 800 mg ekstrak daun tin secara per oral. Kadar flavonoid plasma dianalisis menggunakan HPLC-UV-VIS dengan standar rutin pada serial waktu 0, , 1, 2, 4, 6, 12, dan 24 jam. Hasil pemberian ekstrak daun tin diabsorbsi dan ditemukan dalam plasma darah dengan Cmax 0,016 mg/ml setelah 4 jam pemberian per oral, dengan waktu paruh (t1/2) 7,5 jam dan AUC 0,216 mg jam/ml. Berdasarkan data kadar flavonoid ekstrak daun tin dalam plasma, diperoleh nilai kecepatan absorbsi (Ka) 0,21 mg/jam dan kecepatan eliminasi (K) 0,092 mg/jam. Ekstrak daun tin diabsorbsi lebih cepat dan tereliminasi dari tubuh lebih lama. Keywords: Fig leaf extract; flavonoids; pharmacokinetics; ekstrak daun tin; farmakokinetika; flavonoid